Impact Of Socio-Demographic Factors on Age-Appropriate Immunization of Infants in Slums of Amritsar City (Punjab), India - Gill, KanwalPreet; Devgun, Priyanka (National Journal of Community Medicine, 2015)
Introduction: Vaccination status of slum newborn and infant is far from being satisfactory. Hence, the present study was conducted to assess the age appropriate immunization status of infants and to explore the impact of socio-demographic factors on immunization status in various slum areas of Amritsar city. Methods: A total of 30 clusters of 7 infants each were studied to make a sample of 210 units. Age appropriate immunization status of infants and socio-demographic factors related to it were studied. Results: Out of 210 infants, 42.9% infants were completely immunized appropriate to their age, 27.1% were partially immunized and 30% were unimmunized. On bivariate analysis, age and birth order of infants, nativity, socio-economic status, place of delivery, planning of pregnancy, literacy status of mothers and fathers were statistically significant factors influencing age appropriate immunization. But, on multivariate logistic regression analysis, only age of the child (OR= 2.8, CI= 1.4 to 5.4, p= 0.002) and nativity (OR= 2.0, CI= 1.04 to 3.9, p= 0.04) emerged as significant factors affecting age appropriate immunization. Conclusion: Age appropriate immunization of infants in slums remains very low especially infants of more than six months of age and infants belonging to migrant families.